2019
DOI: 10.1016/j.eplepsyres.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond depression: The impact of executive functioning on quality of life in patients with temporal lobe epilepsy

Abstract: Objective: Individuals with temporal lobe epilepsy (TLE) often experience diminished quality of life (QoL). Although comorbid depression is one of the most recognized predictors of poor QoL in TLE, impairments in verbal memory (VM) and executive functioning (EF), have also been identified as risk factors, independent of other biological and psychosocial factors. In this study, we examine the contribution of depression, VM, and EF to QoL in 52 well-characterized medically-refractory TLE patients. Methods: Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Executive function measures were included in variable selection because neuropsychological studies in major depressive disorder (MDD) have reported executive functioning deficits, and executive dysfunction has been shown to affect the quality of life of patients with TLE, even when controlling for psychiatric comorbidities. 28,35 However, our study shows the inverse relationship; patients who perform better on the verbal fluency test preoperatively are more likely to develop postoperative depression. In our sample, patients who had declines in verbal fluency postoperatively were marginally more likely to experience mood decline that those who did not have verbal fluency worsening.…”
Section: Contribution Of Cognition and Seizure Outcome To Moodmentioning
confidence: 59%
See 1 more Smart Citation
“…Executive function measures were included in variable selection because neuropsychological studies in major depressive disorder (MDD) have reported executive functioning deficits, and executive dysfunction has been shown to affect the quality of life of patients with TLE, even when controlling for psychiatric comorbidities. 28,35 However, our study shows the inverse relationship; patients who perform better on the verbal fluency test preoperatively are more likely to develop postoperative depression. In our sample, patients who had declines in verbal fluency postoperatively were marginally more likely to experience mood decline that those who did not have verbal fluency worsening.…”
Section: Contribution Of Cognition and Seizure Outcome To Moodmentioning
confidence: 59%
“…The verbal fluency test requires patients to name as many words as they can that begin with each of three letters (F‐A‐S) within a given time frame. Executive function measures were included in variable selection because neuropsychological studies in major depressive disorder (MDD) have reported executive functioning deficits, and executive dysfunction has been shown to affect the quality of life of patients with TLE, even when controlling for psychiatric comorbidities 28,35 . However, our study shows the inverse relationship; patients who perform better on the verbal fluency test preoperatively are more likely to develop postoperative depression.…”
Section: Discussionmentioning
confidence: 71%
“…1). Of all the performed studies, only four were multicenter [15, 1921], all the others were single center and cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…A study from the USA of refractory focal epilepsy subjects showed that depression had poorer health perception and reported lower QOL in various domains. 27 In another study, common mental disorders significantly affecting disability were PTSD, MDD, Psychosis(BPAD) and GAD. 28 Schizophrenia and affective psychosis had the highest degree of disability; young age of onset, poor medication adherence and failure of symptom remission as strong predictors of disability.…”
Section: Discussionmentioning
confidence: 99%